2014
DOI: 10.1136/archdischild-2013-305740
|View full text |Cite
|
Sign up to set email alerts
|

Can we distinguish pneumonia from wheezy diseases in tachypnoeic children under low-resource conditions? A prospective observational study in four Indian hospitals

Abstract: Current tachypnoea-based algorithms significantly overdiagnose pneumonia in children and underdiagnose wheezy diseases. Diagnostic accuracy can be improved by various combinations of clinical variables, but the best single diagnostic predictor is auscultation. Simple criteria can also be defined that reliably detect which tachypnoeic children are at high risk of death or deterioration. Management plans based on these protocols could reduce unnecessary antibiotic use, improve the management of wheezy diseases a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
21
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 24 publications
2
21
1
Order By: Relevance
“…The current study in India did not report the proportion of participants who were treated with antibiotics or whether wheeze was used by the treating clinicians as the indication to withhold antibiotics 1. Therefore, no conclusion can be drawn about the safety of using wheeze heard by auscultation to make antibiotic decisions.…”
mentioning
confidence: 83%
See 3 more Smart Citations
“…The current study in India did not report the proportion of participants who were treated with antibiotics or whether wheeze was used by the treating clinicians as the indication to withhold antibiotics 1. Therefore, no conclusion can be drawn about the safety of using wheeze heard by auscultation to make antibiotic decisions.…”
mentioning
confidence: 83%
“…These guidelines include the differential diagnosis of cough and difficult breathing, and separate guidelines for the management of pneumonia, bronchiolitis and asthma. This recognises the core issue behind the study in this edition of Archives by Dr Vishwanath Gowraiah and colleagues from four hospitals in India; that many children who fulfil WHO's traditional criteria for pneumonia (cough and difficult breathing with or without chest in-drawing) have wheezy viral infections 1. The WHO guideline, contained in the second edition of the Pocket Book of Hospital Care for Children ,2 lists the clinical features in favour of pneumonia, bronchiolitis, asthma and other common and less common causes of cough and respiratory distress.…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…That re‐evaluation determined that the diagnosis of pneumonia was not supported in 40% of the patients, and antibiotics were judged to be unnecessarily given in 85%. An observational study at four hospitals in India of 516 children under 6 years of age diagnosed as pneumonia based on WHO criteria found that 43% had what was called “wheezy disease,” more consistent with asthma or bronchiolitis than pneumonia …”
mentioning
confidence: 99%